Ativação das células hepáticas estreladas e fibrose hepática em crianças portadoras de hepatite autoimune tipo 1: estudo imuno-histoquímico de biópsias hepáticas pareadas antes do tratamento e após a remissão clínica - Maia, Jussara Melo de Cerqueira (2009)
The activation of hepatic stellate cells (HSC) is considered the most important event in hepatic fibrogenesis. The precise mechanism of this process is unknown in autoimmune hepatitis (AIH), and more evidence is needed on the evolution of fibrosis. The aim of this study was to assess these aspects in children with type 1 AIH. We analyzed 16 liver biopsy samples from eight patients, paired before treatment and after clinical remission, performed an immunohistochemical study with anti-actin smooth muscle antibody and graded fibrosisand inflammation on a scale of 0:4 (Batts and Ludwig scoring system). We observedthere was no significant reduction in fibrosis scores after 24± 18 months (2.5 ± 0.93 vs. 2.0± 0.53, P = 0.2012). There was an important decrease in inflammation: portal (2.6 ±0.74 vs. 1.3± 0.89, P = 0.0277), periportal/periseptal (3.0 ±0.76 vs. 1.4 ± 1.06, P = 0.0277), and lobular (2.8 ± 1.04 vs. 0.9± 0.99, P =0.0179). Anti-actin smooth muscle antibodies were expressed in the HSC of the initial biopsies (3491.93 ±2051.48 lm2), showing a significant reduction after remission (377.91 ±439.47 lm2) (P = 0.0117). HSC activation was demonstrated in the AIH of children. The reduction of this activation after clinical remission, which may precede a decrease in fibrosis, opens important perspectives in the follow-up of AIH.